P-294 Use of Artificial Intelligence to Assess the Effects of Assisted Hatching on Embryo Development and Implantation Potential. (30th June 2022) - Jiang, V; Bormann, C; Souter, I; Dimitriadis, I; Kanakasabapathy, M.K; Thirumalaraju, P; Shafiee, H
Abstract: Study question: Does the use of laser-assisted hatching (AH) on cleavage stage embryos affect in vitro preimplantation embryo development or implantation potential? Summary answer: There is no difference in blastocyst conversion rate or implantation potential of embryos following AH at the cleavage stage for patients under age 35 years. What is known already: Laser-AH is the process of creating an opening within the zona pellucida on cleavage stage embryos to facilitate biopsy of trophectoderm cells for preimplantation genetic testing (PGT). Studies have shown that PGT for aneuploidy (PGT-A) in patients under 35 years have reduced pregnancy rates compared to those not undergoing biopsy. This is attributed to the additional micromanipulation events involved with PGT-A may decrease the viability of embryos and compromise their implantation potential. We aimed to objectively compare the impact of AH on embryo development using an artificial intelligence (AI)-algorithm trained to assess embryo quality and predict developmental fate. Study design, size, duration: A retrospective dataset from patients under 35 years was generated from two timepoints: cleavage stage embryos immediately before AH between 60-64 hours post insemination (hpi); and blastocyst stage embryos between 110-115 hpi prior to transfer or vitrification. Time-lapse imaging was obtained using the EmbryoScope (Vitrolife). Cleavage stage embryo images were used to train a convolutional neural networks (CNN) to predict and classify the development and implantation potential of cleavage and blastocyst stage embryos. Participants/materials, setting, methods: Time-lapse images were collected for 1444 cleavage stage embryos spanning 189 in vitro fertilization (IVF) cycles between January 2014 – December 2021 at a single academic fertility center in Boston. Embryos were categorized into two groups: Day 3 embryos with AH (D3+AH) and without AH (D3-No AH). Each patient had a single blastocyst embryo transfer with a known outcome. Two-tailed t-tests were used to compare differences, with p-value less than 0.05 set for statistical significance. Main results and the role of chance: The dataset included 1035 embryos with AH (D3+AH) and 409 embryos without AH (D3-No AH). There were no differences in AI-predicted blastocyst development between Day 3 embryos with AH and without AH (64.1% vs 64.1%) or AI-predicted high quality blastocyst development rate between these two groups (43.8% vs 40.8%), respectively. On Day 5 there were no differences in the AI-categorization of embryos at the blastocyst stage between embryos with or without AH (62.3% vs 62.5%) or AI-categorization of high-quality blastocyst development (45.2% vs 41.8%), respectively. AI predicted a similar implantation potential between embryos with and without AH at the cleavage stage (61.1% vs 69.9%). When stratifying to only the embryos transferred, there were no differences in the AI-predicted blastocyst development between Day 3 embryos with AH and without AH (96.0% vs 97.1%) or in the AI-predicted high quality blastocyst development rate between these two groups (72.0% vs 82.7%). AI predicted a similar implantation potential between embryos with and without AH at the cleavage stage (72.0% vs 69.0%). These results correspond with the true clinical pregnancy rate between the AH and Non-AH groups (68.0% vs 61.9%, p = 0.44). Limitations, reasons for caution: These retrospective findings were of patients who had time-lapse imaging of cleavage stage and blastocysts available. Additionally, we focused on high prognosis patients that were eligible for single blastocyst stage embryo transfer. Clinical pregnancy rate was examined, not spontaneous abortion or live birth rates. Wider implications of the findings: Utilization of AI technology allows for more objective and standardized methods for examining the impact of laboratory procedures on the developmental fate of embryos. This study demonstrated the safety of utilizing laser-assisted hatching on embryo development within this study population. Trial registration number: None